Influence of Optical Fiber Parameters on the Speckle Pattern and Spectral Observation in Astronomy - Anzhi Wang; Jiabin Wang; Zhaoxv Gan; Gang Yue; Xvdong Chen; Qi Yan; Shengjia Wang; Yunxiang Yan; Tao Geng; Shuang Chen; Weimin Sun (Photonics)
Optical fibers serve as a bridge to transmit starlight into the spectrograph in fiber spectral surveys. Due to the interference between multiple modes supported within the fiber, a granular speckle pattern appears on the end of the fiber and leads to an uneven and random energy distribution in the spectrum. This effect is called mode noise, which reduces the accuracy of high-resolution spectral detection. This work investigates the influence of transmitted mode numbers on speckle patterns by using fibers with different core diameters and numerical apertures. A reciprocating mechanical scrambler is proposed for suppressing near-field speckles with negligible focal ratio degradation. We use centroid offset and radial power spectrum to quantitatively evaluate the characteristics of the speckles with and without scrambling. Experimental results show that more modes in a fiber with a larger core diameter reduce the centroid offset of the speckle and make the energy distribution more uniform. The mechanical mode scrambler significantly reduces the random centroid deviation caused by speckles, which is more obvious for large-core fibers. The standard deviation of centroid offset in 1000-cycle tests for the 160 µm core fiber is only 0.043 µm, which is one-tenth of that for the 16 µm core fiber. However, in solar spectrum measurement using these fibers, small-core fibers can more easily achieve higher spectral resolution and capture more spectral information. Therefore, large-core fibers are suitable for tasks requiring high accuracy, while fibers with a smaller core diameter should be applied for high-precision spectral measurement.